MANAGERIAL COMPETENCE IN CHURCH STEWARDSHIP - Hutauruk, Johnson Alvonco; Saputra, Yudha Nata (Ridwan Institute, 2024)
The problem of mismanagement in church stewardship is caused by church leaders not being standardized in their managerial competencies which causes them to be unable to carry out their management functions, namely: planning, organizing, actuating, and controlling. This study addresses a notable gap in existing literature by providing a framework that links these competencies to the successful achievement of a church's vision, mission, and goals. The author proposes generic managerial competencies that must be standardized or possessed by the church leaders, such as General Ability, Willingness to do more, Creative Leadership, Goal & Objective Setting, Managerial, Emotional Quotient, Personality, human relations, work style, Loyalty, Work Potential. Finally, the research offers practical insights for church leaders enabling them to enhance their managerial skills and improve overall church governance and operational effectiveness.